The Impact of Personal and Corporate Taxation on Capital Structure Choices - Dennis Voeller; Michael Overesch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper empirically analyses whether both personal and corporate taxation have an impact on companies' capital structure decisions. We investigate the effect of the difference in taxation of debt and equity financing on capital structures. Our empirical results, based on a comprehensive panel of European firm-level data, suggest that a higher tax benefit of debt has the expected significant positive impact on a company's financial leverage. Particularly, we find evidence that the capital structures of smaller companies respond more heavily to changes in the tax benefit of debt. Additional analysis confirms that not only corporate taxes are relevant for corporate financial planning, but variation in capital income tax rates at the shareholder level implicates significant capital structure adjustments as well. Moreover, we find substitutive relationships between non-debt tax shields and the effect of the corporate tax rate on capital structures.
Keywords: G30; H25; G32; H24; 330; Capital Structure; Corporate Income Tax; Personal Income Tax; Firm-Level Data; Kapitalstruktur; Unternehmensbesteuerung; Einkommensteuer; Körperschaftsteuer; Fremdkapital; Steuerwirkung; EU-Staaten